Miron Radu Paraschivescu: cronica unei iubiri anunţate. Misteriosul caiet Vera - Petruța Stan (Revista de Istorie și Teorie Literară)
Here we have the unusually short and intense diary of a love story with three heroes: a woman and two men; two poets and a sculptor. Some of the involved persons are lost in the land of shadows (Miron Radu Paraschivescu, Lena Paraschivescu, Gheorghe Apostu). Sufferance, love, disappointment, desperation have lost their intensity and puriffied themselves in front of the implacable time. It is just a simple blue copybook. A poet talks about the love of his life just in the same moment when he expects a child from another woman.